PENINGKATAN ASPEK PENGETAHUAN DAN PERILAKU ANAK SEKOLAH DASAR/MADRASAH IBTIDAIYAH MELALUI KOMIK BUSKI PADA TIGA DESA ENDEMIS FASCIOLOPSIS BUSKI DI KABUPATEN HULU SUNGAI UTARA, TAHUN 2003 - Anorital, Anorital; Kasnodihardjo, Kasnodihardjo; Dewi, Rita M.; Ompusunggu, Sahat (Badan Penelitian dan Pengembangan Kesehatan, 2008)
Fasciolopsiosis is worm disease which is caused Fasciolopsis buski. The disease is an endemic at some villages in Hulu Sungai Utara Regency with prevalence 1.2-7.8%.The patients are children with age around 1-15 years old. In the year 2002-2003 have been carried out a research